Izzy at the end of the world - Reynolds, K. A. (New York, NY : Clarion Books, 2023)
"An autistic girl faced with disaster, Izzy Wilder and her dog Akka set out to discover the truth behind humanity's disappearance, facing life's greatest mysteries as they uncover the true endurance of the human spirit to save the world"--OCLC.
Bulletin (Center for Children's Books)
Kirkus Review
Publishers Weekly
Bulletin (Center for Children's Books), December 2022
Kirkus Review, December 2022
Publishers Weekly, December 2022
Keywords: Autistic children -- Juvenile fiction; Dogs -- Juvenile fiction; End of the world -- Juvenile fiction; Autistic children -- Fiction; Dogs -- Fiction; End of the world -- Fiction; Autistic children -- Fiction; Dogs -- Fiction; End of the world -- Fiction; Animal fiction; Apocalyptic fiction; Science fiction